A teacher and his students: child Holocaust testimonies from early postwar Polish Bytom. Issue 1 (2nd January 2016) - Cohen, Boaz; Müller, Beate
ABSTRACT: The document presented here was created in 1945 in Bytom, Poland. It contains testimonies by Holocaust survivor children collected and put down in a notebook by their survivor teacher, Shlomo Tsam, in the immediate aftermath of the Holocaust. The testimonies shed light on Jewish children's experience in Eastern Europe during the Holocaust, describing oppression, flight, and survival in the words of the weakest segment of Jewish communities – children. The testimonies provide raw data on the encounters between Jews and non-Jews in the territories in which the "Final Solution" was carried out. It is thus an important source contributing to the burgeoning research on the involvement of local populations in the murder of the Jews, on one hand, and in saving Jews, on the other. The creation of this document, one of several collections of Jewish survivor children's testimonies produced in the immediate postwar years, is also indicative of post-Holocaust Jewish sensibilities and concerns regarding surviving children.